The use of Technology to Ensure the Quality of Teaching and Learning: Senior High School Teachersâ Perspective - Mustafa, M. Nur; Zulhafizh, Zulhafizh (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research aims to observe and analyze the use of technology to ensure the quality of teaching and learning by teachers. Technology plays an important role in teaching and learning activities. The maximum and effective use of technology encourages the achievement of the expected goals. This research focused on 108 senior high school teachers. Data of this research are collected through questionnaires filled in by the respondents. The data were then analyzed by using the descriptive approach, SPSS version 21 and Microsoft Excel. The research findings reveal that teachersâ orientation in using technology to ensure the quality of teaching and learning is making use of technology a medium to support teaching and learning activities, learning and following the current development of IT from various sources, making use of computers or projector for teaching and learning activities, and making use of programs or software to analyze learning outcomes. The average of effort made by the teachers is 4.25 (very high standard). It is an innovative strategy by senior high school teachers to maintain and even to increase teaching and learning standard so that learning goals can be achieved.